The roles of managerial overconfidence on the firm's leverage / Siti Rahayu Beli - Beli, Siti Rahayu (2021)
Based on the cognitive psychology literature, irrational behaviour includes the human inability to predict how likely future outcomes are. Managers tend to display irrational behaviour, especially in making an important decision such as financing decision. As a result, they seem to overestimate or underestimate in making capital structure decision. Overestimating is closely related to their personal actions and closely related to overconfidence. Since managers made the firm's decision, it is necessary to investigate the effects of their overconfidence on debt financing. The purpose of this study is to investigate the effect of managerial overconfidence and firm-specific characteristics on firm's leverage for public listed companies in Bursa Malaysia. Additionally, this study also aimed to examine the moderating effect of managerial overconfidence between firm-specific characteristics and firm's leverage which are not adequately addressed in the previous studies. In this study, the researcher employed static panel regression to analyse the data and mainly focus on a single industry only, which is Industrial Products and Services Sector. The period of study is seven years, whereby the data was collected from the year 2012 until 2018. The analysis has two parts, first by conducting analysis on Overall Industrial Products and Services sector, followed by analysis by sub-sector. The result that the researcher found from this study are managerial overconfidence had a significant effect on the firm's leverage for Overall Industrial Products and Services and its sub-sector of Building Materials, Diversified Industrials and Chemicals. As for moderation factor, it was found that managerial overconfidence has a moderating effect in influencing the relationship between firm-specific characteristics and firm's leverage in the Overall Industrial Products and Services. The same result obtained in its sub-sector of Building Materials, Wood and Wood Products and Diversified Industrials. The finding of this research reflects the importance of behavioural bias which is overconfidence in determining the firm's leverage.